The epilepsies : etiologies and prevention - Kotagal, Prakash; Luders, Hans (Academic Press, 1999)
Tremendous advances in our understanding of epilepsy have occurred in the last two decades. Techniques such as electroencephalography, neuroimaging, neurosurgery and neuropsychology are giving us a better understanding of the pathogenesis of epilepsy. Additionally major breakthroughs are taking place in the laboratories of scientists studying genetics, embryogenesis, neuropathology, neurochemistry and pharmacology. These advances provide a much better understanding of why patients develop epilepsy, reshaping the way in which the epileptic patient is cared for. This book presents the most current information on the various etiologies of epilepsy, their treatments, and their possible prevention. Kotagal and Luders have assembled 80 internationally known experts to compile this authoritative, comprehensive, and well-rounded work. The Epilepsies is a one-of-a-kind reference that will be of interest to specialists and basic scientists involved in the study of epilepsy, adult and pediatric neurologists, neurosurgeons, residents and fellows in these areas, and pediatricians who frequently encounter children with neurological problems. This major work brings together the most up-to-date research on the causes of epilepsy and other associated diseases which cause seizures. It presents data on infections, trauma, mesial temporal sclerosis, cerebral dysgenesis, brain tumors, vascular lesions, stroke, as well as genetic, metabolic and toxic causes of epilepsy. The book also looks at drug treatment and new surgical techniques that have proven useful in alleviating epileptic and other related seizures. Key Features * More than 65 chapters are organized into the following sections: * Cerebral Dysgenesis * Mesial Temporal Sclerosis * Postinfectious Epilepsy * Posttraumatic Epilepsy * Neoplastic Causes of Epilepsy * Vascular Causes of Epilepsy * Non-Heriditary Myoclonic Epilepsy * Metabolic and Toxic Causes of Epilepsy * Etiologies of Neonatal Seizures * Psychogenic Seizures * Genetic Causes of Epilepsy.